An outbreak of bluetongue in sheep - E, Pérez; J, Asín; FA, Uzal (Brazilian Journal of Veterinary Pathology, 2023)
During a 2-week period between mid-October and November 2022, approximately 20 out of 470 Rambouillet sheep from a flock in southern California died; the flock had been moved into irrigated hay fields recently. Some of the affected animals were initially underweight and most had nasal discharge, labored breathing and frothy discharge from the mouth. Two adult sheep (1 and 2) were submitted to the San Bernardino laboratory of the California Animal Health and Food Safety laboratory system (CAHFS) for necropsy and diagnostic work up.